Developing West Kalimantan Folklore Videos for Narrative Text Material - Supriati, Risky; Bunau, Eusabinus; Salam, Urai (FKIP - Universitas Tanjungpura, 2023)
This research aims to enhance the teaching and learning of narrative texts for tenth-grade students by designing West Kalimantan Folklore Videos (WKFV) as supplementary learning materials. The study adopts a development research approach, utilizing the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) procedure to design the materials. The research consists of three phases: analyzing, designing, and developing. In the analyzing phase, an English teacher from MAN 2 Pontianak was interviewed, and a questionnaire was distributed to X IPS 3 students. The WKFV was developed using various software tools such as Canva, Vimeo, WordPress, Google Drive, and Google Forms. An internal evaluation was conducted in the development phase to assess the usability of the WKFV. The results of the internal evaluation demonstrated that the WKFV met all the required criteria. In conclusion, the WKFV proves to be a practical and effective tool for supporting the teaching and learning of narrative texts.